IMPROVING EDUCATION AND TRAINING IN BASIC CARDIOPULMONARY RESUSCITATION: NEW RESEARCH AND PERSPECTIVES (Education in the 21st Century, 2023)
It is widely admitted that education and training are the effective modalities that substantially improve resuscitation care for cardiac arrest. The high quality cardiopulmonary resuscitation (CPR), including early recognition of cardiac arrest, adequate chest compressions, opening of the airway and rescue breathing, are important determinants of successful outcome in cardiac arrest patients.The aim should be to develop teaching strategies for general public and healthcare professionals to deliver effective CPR and defibrillation to save more lives.Education in resuscitation is still a relatively new field lacking high quality research. Studies are heterogeneous in design and difficult to compare.Our approach to education is constantly changing. Methods for teaching have changed substantially over the years and continue to evolve.This paper provides review of available literature regarding education in resuscitation. It also reviews the new Guidelines for Resuscitation of the European Resuscitation Council (ERC), American Heart Association (AHA) and International Liaison Committee on Resuscitation (ILCOR), focusing on the most important changes in recommendations for education and training. It also summarises the ERC basic principles of education and implementation of resuscitation, providing the basis for improving CPR education.The review of the above available sources nonetheless confirms there is still a shortage of evidence about the best methods of teaching. Until the time that statistical significance is achieved, it is essential that we continue to evaluate our educational methods and assess the educational importance or relevance of the findings.
Keywords: Keywords: basic cardiopulmonary resuscitation (CPR), effective CPR education and training.